Acculturation of Arabic Language on Hijrah Muslim Communication Oriented The Articulation of Islamic Identity - Syarifah Rahmi; Julhadi; M. Riyan Hidayat; Ahmad Hariyadi; Ahmad Helwani Syafi’i (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Arabic is the basic foundation in Islam both scientifically and in practice. The reason is, the Qur'an and al-Hadith use Arabic as the medium of delivery. Recently, there has been an expansion of the function of the Arabic language which is brought into the realm of daily communication in order to articulate Islamic identity and mostly occurs in the Muslim community of hijra. This research is a qualitative descriptive study. The implementation procedure is to observe the reality of the arabization of the communication of the hijrah Muslim community and its relationship to the articulation of Islamic identity. The method used in analyzing the data is Miles and Huberman's interactive model, namely; data reduction, data presentation, drawing conclusions. While the method used in testing the validity of the data is the method of triangulation and triangulation of sources, peer discussions and member check. The results of this study are: 1) Arabicization of the communication of the hijrah Muslim community is a process of assimilation of Arabic in culture and is used as a symbol in identity politics in a global society. 2) The Arabization of this communication does not touch fundamental aspects of Islam at all, but is only a model of communication.